Oxalic Acid Production in Clarireedia jacksonii Is Dictated by pH, Host Tissue, and Xylan - Townsend, Ronald V.; Rioux, Renee A.; Kabbage, Mehdi; Stephens, Cameron; Kerns, James P.; Koch, Paul (Frontiers in Microbiology, 2020)
Dollar spot is caused by the fungus Clarireedia jacksonii and is the most common disease of golf course turfgrass in temperate climates. Oxalic acid (OA) is an important pathogenicity factor in other fungal plant pathogens, such as the dicot pathogen Sclerotinia sclerotiorum, but its role in C. jacksonii pathogenicity on monocot hosts remains unclear. Herein, we assess fungal growth, OA concentration, and pH change in potato dextrose broth (PDB) following incubation of C. jacksonii. In addition, OA production by C. jacksonii and S. sclerotiorum was compared in PDB amended with creeping bentgrass or common plant cell wall components (cellulose, lignin, pectin, or xylan). Our results show that OA production is highly dependent on the environmental pH, with twice as much OA produced at pH 7 than pH 4 and a corresponding decrease in PDB pH from 7 to 5 following 96 h of C. jacksonii incubation. In contrast, no OA was produced or changes in pH observed when C. jacksonii was incubated in PDB at a pH of 4. Interestingly, C. jacksonii increased OA production in response to PDB amended with creeping bentgrass tissue and the cell wall component xylan, a major component of all walls of grasses. S. sclerotiorum produced large amounts of OA relative to C. jacksonii regardless of treatment and no treatment increased OA production by this fungus, though pectin suppressed S. sclerotiorum OA production. These results suggest that OA production by C. jacksonii is reliant on host specific components within the infection court, as well as the ambient pH of the foliar environment during its pathogenic development.